Pengaruh Kecerdasan Intelektual, Kecerdasan Emosional, Kecerdasan Spiritual, dan Perilaku Belajar Terhadap Pemahaman Akuntansi - Gayatri, Ni Putu Laksmi; Wirawati, Ni Gst. Putu (E-Jurnal Akuntansi, 2019)
This research was conducted on regular afternoon students in the accounting department of the Faculty of Economics and Business, Udayana University. This study uses primary data collected using a questionnaire as an instrument for collecting data distributed to respondents. The respondents of this study were regular afternoon students of the 2015 accounting department of the Faculty of Economics and Business, Udayana University. The number of samples obtained was 65 samples. The data analysis technique used is multiple linear regression analysis. The results of the analysis show that the variables of intellectual intelligence, emotional intelligence, spiritual intelligence, and learning behavior have positive and statistically significant effects on the understanding of accounting. This means that the better the intellectual intelligence, emotional intelligence, spiritual intelligence, and learning behavior, the better the understanding of accounting. Keywords : Intellectual intelligence, emotional intelligence, spiritual intelligence, learning behavior, understanding of accounting.